2019
DOI: 10.7150/ijms.34541
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of CDK12 protein in gastric cancer and its positive correlation with CD8+ cell density and CCL12 expression

Abstract: Background:The aims of this study were to investigate the expression pattern of CDK12 protein in gastric cancer, and to analyze the correlations of CDK12 expression between CD8 + cell density and CCL12 expression. Methods: Eighty-six paired tumor and non-tumor samples were collected from patients who underwent radical surgery and had pathological confirmed gastric adenocarcinoma. Immunohistochemistry was used to assess CDK12 expression and CD8 + cell density. Expression of CDK12 and CCL21 mRNA was detected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Moreover, patients with high expression of CDK12 show lower overall survival rates than patients with low expression of CDK12 [75]. They have identified positive correlations of CD8+ cell number and CCL21 (CC-chemokine ligand 21) mRNA expression with CDK12 level [75]. These evidences indicate the involvement of CDK12 in gastric cancer.…”
Section: Cdk12 In Gastric Cancermentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, patients with high expression of CDK12 show lower overall survival rates than patients with low expression of CDK12 [75]. They have identified positive correlations of CD8+ cell number and CCL21 (CC-chemokine ligand 21) mRNA expression with CDK12 level [75]. These evidences indicate the involvement of CDK12 in gastric cancer.…”
Section: Cdk12 In Gastric Cancermentioning
confidence: 93%
“…Among these, CDK12 amplification is mainly detected in HER2-positive gastric cancer [74]. Ji et al have shown that high-level expression of CDK12 is detected in gastric tumor samples compared with normal samples [75]. Moreover, patients with high expression of CDK12 show lower overall survival rates than patients with low expression of CDK12 [75].…”
Section: Cdk12 In Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…CDK12 has been implicated in cancer pathology, such as cell invasion, suggesting that aberrant CDK12 expression may have oncogenic properties. Thus, this kinase may become a particularly interesting therapeutic target in prostate [ 128 ], esophageal [ 129 ], gastric [ 130 ], breast [ 131 ], endometrial, bladder, uterine, and ovarian [ 132 ], pancreatic [ 133 ], non-small cell lung cancer [ 134 ], lung adenocarcinoma [ 135 ], and follicular lymphoma [ 136 ]. An increasing number of studies point to the role of CDK12, in cell function and cancer, as an effective strategy to inhibit tumor growth, and its potential clinical use as a biomarker.…”
Section: Cyclin-dependent Kinases (Cdks)mentioning
confidence: 99%
“…CCL21 is a member of the CC chemokines that has been reported to co-localize the dendritic cells and lymphocytes, emphasizing its promise as a therapeutic target for human solid cancers [ 8 ]. Moreover, CCL21 has been previously documented to be overexpressed in GC [ 9 ], highlighting its potential oncogenic role in this malignancy. However, to date, the potential mechanism by which CCL21 influences GC remains undefined.…”
Section: Introductionmentioning
confidence: 99%